The importance of contemporary social sciences in Latin America - Mejía Navarrete, Julio (2021)
The article analyzes the process of theoretical originalization in Latin America that announces the exploration of another sense of history, anointed in the unity of the social sciences, the development of new research problems and the development of alternative discourses.